Electrolyte and lithium ion battery
Patent Information
- Application Number
- CN202311867518.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-29
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-12-29
AI Technical Summary
大容量锂离子电池散热条件差,热量容易累计使电芯温度升高
[0030]本发明提供一种同时含有添加剂A和添加剂B的电解液。添加剂A含有醚链,可以在负极界面参与形成有利于Li+脱溶剂化的SEI膜、降低界面阻抗;同时,添加剂A参与形成的SEI膜具有较好的机械强度,可以缓解充放电过程中负极体积变化对SEI膜的破坏作用,但添加剂A形成的SEI膜热稳定性较差。添加剂B参与形成的SEI膜具有较好的热稳定性,可以改善高温循环和存储性能;但添加剂B形成SEI膜阻抗较大。本发明同时添加剂A和添加剂B,添加剂A优先于添加剂B发生还原分解,二者参与形成醚链化合物和含氮化合物彼此交叠的SEI膜,醚链化合物具有良好的机械强度和粘附性,防止充放电过程中负极体积变化导致含氮化合物脱落,含氮化合物良好的热稳定性和化学稳定性稳定醚链的结构,抑制醚链发生热分解和HF等的破坏;同时添加剂A的还原分解可以抑制添加剂B过度参与SEI膜形成导致阻抗增加;两者协同作用形成低阻抗、高热稳定性的SEI膜。
Smart Images

Figure CN117832617B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery technology, specifically relating to electrolytes and lithium-ion batteries. Background Technology
[0002] In recent years, the national dual-carbon strategy has driven the vigorous development of the new energy and energy storage industries. As an important part of the energy storage industry, the cycle performance of lithium-ion batteries is a focus of attention. Large-capacity lithium-ion batteries have poor heat dissipation conditions, and heat easily accumulates, causing the cell temperature to rise. Under high-temperature conditions, the battery's SEI film (Solid Electrolyte Interface) is prone to decomposition and damage, which exacerbates internal side reactions within the cell, leading to deterioration in cycle efficiency and accelerated capacity decay. Summary of the Invention
[0003] To address the problems of the prior art, the present invention provides an electrolyte comprising additive A and additive B, wherein additive A is selected from one or more compounds of formula I, and additive B is selected from one or more nitrogen-containing heterocyclic compounds.
[0004]
[0005] R1, R2, R3, and R4 are independently selected from methyl, ethyl, propyl, methoxy, ethoxy, propoxy, or -(-CH2-)n1-(-O-(-CH2-)n2-)n3-(-CH2-)n4-CH3, and at least one of R1, R2, R3, and R4 is selected from -(-CH2-)n1-(-O-(-CH2-)n2-)n3-(-CH2-)n4-CH3; n1 is an integer from 0 to 5, n2 is an integer from 1 to 3, n3 is an integer from 1 to 5, and n4 is an integer from 0 to 5.
[0006] According to a specific embodiment of the present invention, the nitrogen-containing heterocyclic compound is selected from one or more of pyridine compounds, pyrazine compounds, and pyridazine compounds.
[0007] According to a specific embodiment of the present invention, the nitrogen-containing heterocyclic compound is selected from one or more compounds with the structure of formula II-1, formula II-2, and formula II-3;
[0008]
[0009] Among them, R5, R6, R7, R8, R9, R 10 R 11 R 12 R 13 R 14 R 15 R 16 R17 Each can be independently classified as one of the following: hydrogen group, fluorine group, methyl group, or trifluoromethyl group.
[0010] According to a specific embodiment of the present invention, additive A is selected from one or more of the following compounds:
[0011]
[0012]
[0013] According to a specific embodiment of the present invention, additive B is selected from one or more of the following compounds:
[0014]
[0015]
[0016] According to a specific embodiment of the present invention, the electrolyte includes at least two additive compounds A and / or at least two additive compounds B.
[0017] Preferably, the electrolyte includes at least two of additives A1 to A10; more preferably, the electrolyte includes additive A1 and additive A4, or additive A4 and additive A5.
[0018] Preferably, the electrolyte includes at least two of additives B1 to B12; more preferably, the electrolyte includes additives B5 and B12.
[0019] More preferably, the electrolyte includes additives A4 and A5, as well as additives B5 and B12.
[0020] According to a specific embodiment of the present invention, the total mass percentage a of additive A and the total mass percentage b of additive B in the electrolyte satisfy: 0.25≤a / (b+t0)≤4, where t0=0.01%, t0 has no meaning, it is just that in the comparative example there is no additive B, that is, b=0, and a small value t0 is added to b.
[0021] Wherein, the total mass percentage a of additive A in the electrolyte satisfies 0.05% ≤ a ≤ 2%, preferably 0.1% ≤ a ≤ 1.6%; and / or, the total mass percentage b of additive B in the electrolyte satisfies 0.05% ≤ b ≤ 2%, preferably 0.1% ≤ b ≤ 1.6%.
[0022] According to a specific embodiment of the present invention, the electrolyte further includes a solvent, a lithium salt, and an additive C, wherein the weight of the lithium salt is 10-20% of the total weight of the electrolyte.
[0023] According to a specific embodiment of the present invention, the lithium salt includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorophosphate, lithium difluorooxalate borate, lithium difluorooxalate phosphate, lithium bis(fluorosulfonyl)imide, lithium methanesulfonate, lithium bis(oxalate borate), and lithium perchlorate.
[0024] According to a specific embodiment of the present invention, the lithium salt is any one of lithium hexafluorophosphate, a combination of lithium hexafluorophosphate and lithium difluorosulfonylimide, or a combination of lithium hexafluorophosphate and lithium difluorooxalate borate.
[0025] According to a specific embodiment of the present invention, the solvent includes one or more of ethylene carbonate, fluoroethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, propyl acetate, ethyl acetate, and propyl propionate.
[0026] According to a specific embodiment of the present invention, additive C is selected from one or more of fluoroethylene carbonate, vinylene carbonate, methylene disulfonate, 1,3-propanesulfonyl lactone, 1,4-butanesulfonyl lactone, 1,3-propenesulfonate lactone, vinyl sulfate, propylene sulfate, sulfone, and polyethersulfone. The weight of additive C is 1-5% of the total weight of the electrolyte.
[0027] Another object of the present invention is to provide a lithium-ion battery, comprising a negative electrode, a positive electrode, a separator, and the electrolyte described above.
[0028] The negative electrode, positive electrode, and separator included in the technical solution of the present invention are conventional negative electrodes, positive electrodes, and separators in the art.
[0029] Beneficial effects:
[0030] This invention provides an electrolyte containing both additive A and additive B. Additive A contains an ether chain, which can participate in the formation of a favorable Li-type electrolyte at the negative electrode interface. +The desolvated SEI film reduces interfacial impedance. Simultaneously, the SEI film formed with additive A exhibits good mechanical strength, mitigating the destructive effects of negative electrode volume changes during charge and discharge. However, the SEI film formed with additive A has poor thermal stability. The SEI film formed with additive B exhibits good thermal stability, improving high-temperature cycling and storage performance; however, the SEI film formed with additive B has higher impedance. This invention utilizes both additives A and B, with additive A preferentially undergoing reductive decomposition before additive B. Both participate in the formation of an SEI film composed of overlapping ether chain compounds and nitrogen-containing compounds. The ether chain compounds possess good mechanical strength and adhesion, preventing nitrogen-containing compounds from detaching due to negative electrode volume changes during charge and discharge. The good thermal and chemical stability of the nitrogen-containing compounds stabilizes the ether chain structure, inhibiting thermal decomposition and damage from HF, etc. Simultaneously, the reductive decomposition of additive A inhibits excessive participation of additive B in SEI film formation, preventing increased impedance. The synergistic effect of both additives forms a low-impedance, high-thermal-stability SEI film. Detailed Implementation
[0031] The present invention will now be described in detail with reference to specific embodiments.
[0032] This invention provides an electrolyte comprising additive A and additive B, wherein additive A is selected from one or more compounds of formula I, and additive B is selected from one or more nitrogen-containing heterocyclic compounds;
[0033]
[0034]
[0035] R1, R2, R3, and R4 are independently selected from methyl, ethyl, propyl, methoxy, ethoxy, propoxy, or -(-CH2-)n1-(-O-(-CH2-)n2-)n3-(-CH2-)n4-CH3, and at least one of R1, R2, R3, and R4 is selected from -(-CH2-)n1-(-O-(-CH2-)n2-)n3-(-CH2-)n4-CH3; n1 is an integer from 0 to 5, n2 is an integer from 1 to 3, n3 is an integer from 1 to 5, and n4 is an integer from 0 to 5.
[0036] According to a specific embodiment of the present invention, the nitrogen-containing heterocyclic compound is selected from one or more of pyridine compounds, pyrazine compounds, and pyridazine compounds.
[0037] According to a specific embodiment of the present invention, the nitrogen-containing heterocyclic compound is selected from one or more compounds with the structure of formula II-1, formula II-2, and formula II-3;
[0038]
[0039] Among them, R5, R6, R7, R8, R9, R 10 R 11 R 12 R 13 R 14 R 15 R 16 R 17 Each can be independently classified as one of the following: hydrogen group, fluorine group, methyl group, or trifluoromethyl group.
[0040] According to a specific embodiment of the present invention, additive A is selected from one or more of the following compounds:
[0041]
[0042]
[0043] According to a specific embodiment of the present invention, additive B is selected from one or more of the following compounds:
[0044]
[0045]
[0046] According to a specific embodiment of the present invention, the electrolyte includes at least two additive compounds A and / or at least two additive compounds B.
[0047] In the electrolyte of the present invention, which includes additive A and additive B, the battery prepared by using additive A with two structures or additive B with two structures has better DCR (direct current resistance) performance and high temperature cycling performance than that of additive A or additive B alone.
[0048] Preferably, the electrolyte includes at least two of additives A1 to A10; more preferably, the electrolyte includes additive A1 and additive A4, or additive A4 and additive A5.
[0049] Preferably, the electrolyte includes at least two of additives B1 to B12; more preferably, the electrolyte includes additives B5 and B12.
[0050] More preferably, the electrolyte includes additives A4 and A5, as well as additives B5 and B12.
[0051] According to a specific embodiment of the present invention, the total mass percentage a of additive A and the total mass percentage b of additive B in the electrolyte satisfy: 0.25≤a / (b+t0)≤4, where t0=0.01%.
[0052] When a / (b+t0)≤0.25, the amount of additive B is relatively high, and the SEI film formed by additive B has a large impedance, which increases DCR and thus deteriorates the high temperature cycling performance.
[0053] When a / (b+t0)≥4, the amount of additive A is relatively high, resulting in poor thermal stability of the SEI film and significantly deteriorating high-temperature cycling performance.
[0054] Wherein, the total mass percentage a of additive A in the electrolyte satisfies 0.05% ≤ a ≤ 2%, preferably 0.1% ≤ a ≤ 1.6%; and / or, the total mass percentage b of additive B in the electrolyte satisfies 0.05% ≤ b ≤ 2%, preferably 0.1% ≤ b ≤ 1.6%.
[0055] If the dosage of additive A is too low, it cannot exert a significant improvement effect; if the dosage of additive is too high, the thermal stability of the SEI film formed at high temperatures will decrease, and the high-temperature cycling performance will deteriorate.
[0056] If the amount of additive B is too low, it cannot have a significant improvement effect; if the amount of additive is too high, the resulting SEI film will have high impedance, which will affect energy efficiency and increase the risk of lithium plating on the negative electrode.
[0057] According to a specific embodiment of the present invention, the electrolyte further includes a solvent, a lithium salt, and an additive C, wherein the weight of the lithium salt is 10-20% of the total weight of the electrolyte.
[0058] According to a specific embodiment of the present invention, the lithium salt includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorophosphate, lithium difluorooxalate borate, lithium difluorooxalate phosphate, lithium bis(fluorosulfonyl)imide, lithium methanesulfonate, lithium bis(oxalate borate), and lithium perchlorate.
[0059] According to a specific embodiment of the present invention, the lithium salt is any one of lithium hexafluorophosphate, a combination of lithium hexafluorophosphate and lithium difluorosulfonylimide, or a combination of lithium hexafluorophosphate and lithium difluorooxalate borate.
[0060] According to a specific embodiment of the present invention, the solvent includes one or more of ethylene carbonate, fluoroethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, propyl acetate, ethyl acetate, and propyl propionate.
[0061] According to a specific embodiment of the present invention, additive C is selected from one or more of fluoroethylene carbonate, vinylene carbonate, methylene disulfonate, 1,3-propanesulfonyl lactone, 1,4-butanesulfonyl lactone, 1,3-propenesulfonate lactone, vinyl sulfate, propylene sulfate, sulfone, and polyethersulfone. The weight of additive C is 1-5% of the total weight of the electrolyte.
[0062] Another object of the present invention is to provide a lithium-ion battery, comprising a negative electrode, a positive electrode, a separator, and the electrolyte described above.
[0063] The negative electrode, positive electrode, and separator included in the technical solution of the present invention are conventional negative electrodes, positive electrodes, and separators in the art.
[0064] The embodiments and comparative examples provided below illustrate the implementation of this application in more detail. Various tests and evaluations were conducted according to the methods described below.
[0065] Example 1
[0066] 1. Preparation of the positive electrode sheet:
[0067] The positive electrode active material lithium iron phosphate, conductive agent conductive carbon black, binder polyvinylidene fluoride, etc. are dispersed in the solvent N-methylpyrrolidone and mixed evenly to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil; after drying, cold pressing, slitting, cutting and other processes, the positive electrode sheet is obtained.
[0068] 2. Preparation of the negative electrode sheet:
[0069] The negative electrode active material graphite, conductive agent conductive carbon black, thickener carboxymethyl cellulose and binder styrene-butadiene rubber are dispersed in the solvent N-methylpyrrolidone and mixed evenly to obtain a negative electrode slurry; the negative electrode slurry is coated on the negative electrode current collector aluminum foil; after drying, cold pressing, slitting and cutting, the negative electrode sheet is obtained.
[0070] 3. Preparation of electrolyte:
[0071] In an argon-atmosphere glove box with a moisture content ≤1ppm, ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate solvents are thoroughly mixed in a mass ratio of 1:1:1. Then, the dried electrolyte lithium salt, lithium hexafluorophosphate, is dissolved in the solvent and stirred until completely dissolved. Finally, additives A and B, fluoroethylene carbonate, and vinyl sulfate are added and mixed thoroughly to obtain the electrolyte. Additive A is selected from additive A1, and additive B is selected from additive B1. Based on the mass of the electrolyte, the mass percentages of additive A1 and B1 are 0.3%, 13%, 2%, and 2%, respectively. The remainder is organic solvent.
[0072] 4. Preparation of the separating membrane:
[0073] A 12-micron polyethylene film diaphragm was selected.
[0074] 5. Battery assembly:
[0075] The prepared positive electrode, separator, and negative electrode are stacked in sequence, with the separator positioned between the positive and negative electrodes to separate them. After winding, a bare cell is obtained. After connecting the tabs, the cell is assembled into an outer packaging. The prepared electrolyte is then injected, and the cell is encapsulated, left to stand, formed, shaped, and its capacity is tested to finally produce a lithium-ion battery.
[0076] Examples 2 to 12
[0077] Except for adjusting the type of additive B according to Table 1 in the <Preparation of Electrolyte> section, the rest is the same as in Example 1.
[0078] Examples 13 to 23
[0079] Except for adjusting the contents of additives A1 and B1 according to Table 1 in the <Preparation of Electrolyte> section, the rest is the same as in Example 1.
[0080] Examples 24 to 32
[0081] Except for adjusting the types and contents of additives A and B according to Table 1 in the <Preparation of Electrolyte>, the rest is the same as in Example 1.
[0082] Examples 33 to 35
[0083] Except for adjusting the types and contents of the two additives A or the two additives B according to Table 1 in the <Preparation of Electrolyte>, the rest is the same as in Example 1.
[0084] Comparative Examples 1-5
[0085] Except for the addition of additive A1 or additive B1 according to Table 1 in the <Preparation of Electrolyte> section, and the adjustment of their content, the rest is the same as in Example 1.
[0086] Test methods and equipment
[0087] 1. High-temperature cycling performance test
[0088] (1) The prepared lithium-ion battery was left to stand for 1 hour at 45°C; ① Charged to 3.65V at 1P rate, ② left to stand for 10 minutes, ③ Discharged to 2.5V at 1P rate, ④ left to stand for 10 minutes.
[0089] (2) At 45°C, let the lithium-ion battery treated in step (1) stand for 1 hour; ① charge at 1P rate to 3.65V, ② stand for 10 minutes, ③ discharge at 1P rate to 2.5V, ④ stand for 10 minutes. Record the discharge capacity in step ③ as the initial capacity.
[0090] (3) At 45℃, the lithium-ion battery treated in step (2) was left to stand for 1 hour; ① Charged at 1P rate to 3.65V, ② left to stand for 10 minutes, ③ Discharged at 1P rate to 2.5V, ④ left to stand for 10 minutes; Cyclic performance test was performed according to the above charge and discharge process (①→②→③→④). The retention rate of discharge capacity relative to the initial capacity after 1000 charge and discharge cycles was recorded.
[0091] 2. DCR Test
[0092] (1) The prepared lithium-ion battery was left to stand for 1 hour at 45℃; ① Charged to 3.65V at 1C rate constant current and constant voltage, ② left to stand for 10 minutes, ③ Discharged to 2.5V at 1C rate constant current, ④ left to stand for 10 minutes; Repeat the above charging and discharging process (①→②→③→④) 3 times.
[0093] (2) At 25°C, the lithium-ion battery treated in step (1) was left to stand for 1 hour; ① Charged at a constant current and constant voltage of 0.5C to 3.65V, ② left to stand for 10 minutes, ③ Discharged at a constant current of 0.5C to 2.5V, ④ left to stand for 10 minutes; Repeat the above charging and discharging process (①→②→③→④) 3 times; Record the discharge capacity of the last discharge process as the initial capacity C0;
[0094] (3) Charging DCR: In an environment of 25℃, the lithium-ion battery treated in step (2) was left to stand for 30 min; ① 0.1C constant current charging for 60 min, ② left to stand for 60 min, ③ 1.07C constant current discharging for 30 s, ④ left to stand for 40 s, ⑤ 1.07C constant current charging for 30 s, ⑥ left to stand for 10 min; (⑤ termination voltage - ④ termination voltage) / 1.07C0 is the DCR of this SOC (State of Charge); repeat (①→②→③→④→⑤→⑥) 9 times;
[0095] (4) In an environment of 25℃, after the lithium-ion battery in step (3) is left to stand for 10 minutes, it is charged to 3.65V by constant current and constant voltage at a rate of 0.5C (constant voltage charging cutoff condition, charging current ≤0.05C).
[0096] (5) Discharge DCR: In an environment of 25℃, the lithium-ion battery treated in step (3) is left to stand for 30 min; ① 0.1C rate constant current discharge for 60 min, ② stand for 60 min, ③ 1.07C rate constant current discharge for 30 s, ④ stand for 40 s, ⑤ 1.07C rate constant current charge for 30 s, ⑥ stand for 10 min; (③ termination voltage - ② termination voltage) / 1.07C0 is the DCR of this SOC state; repeat (①→②→③→④→⑤→⑥) 9 times.
[0097] The relevant parameters of Examples 1 to 35 and Comparative Examples 1 to 5 are shown in Table 1:
[0098] Table 1
[0099]
[0100]
[0101]
[0102] The test data for Examples 1 to 35 and Comparative Examples 1 to 5 are shown in Table 2:
[0103] Table 2
[0104]
[0105]
[0106] As can be seen from Table 2, the comparison between Comparative Examples 1-3 and Example 1, and Comparative Examples 1, 4, 5 and 18 shows that using additive A1 alone can improve DCR but deteriorates high-temperature cycling performance, while using additive B1 alone can improve high-temperature cycling performance but deteriorates DCR, and the higher the dosage, the more obvious the deterioration effect. The combination of the two can exert a synergistic effect, improving both DCR and high-temperature cycling performance, with the improvement in high-temperature cycling performance being particularly significant.
[0107] As can be seen from the data in Examples 1 to 12 in Table 2, under the same additive content, in terms of DCR performance, the combination of additive A1 and additive B6 shows the most significant improvement in DCR, meaning that additive B6 is better able to suppress the deterioration effect of DCR. In terms of high-temperature cycling performance, the combination of additive A1 and additive B12 is the best, while the high-temperature cycling performance of combinations of additive A1 with additives B8, B9, and B12 shows little difference. Considering both DCR and high-temperature performance, the combination of additive A1 and additive B1 is superior.
[0108] The comparison between Examples 1 and Examples 13 to 23 shows that the combination of 1.2 wt% additive A1 and 1.2 wt% additive B1 has a more significant effect on improving DCR and high-temperature cycling performance. Further increasing the content of additive A1 and additive B1 will worsen DCR and high-temperature cycling performance.
[0109] The comparison of Examples 1 and Examples 13 to 16 shows that when the content of additive A1 remains unchanged, as the content of additive B1 increases, a / (b+t0) gradually decreases, DCR deteriorates while high-temperature cycling performance improves; when a / (b+t0)≤0.25, further increasing of additive B1 causes DCR to increase rapidly but high-temperature cycling performance begins to deteriorate.
[0110] The comparison between Example 1 and Examples 17 to 23 shows that when the content of additive B1 remains unchanged, as the content of additive A1 increases, a / (b+t0) gradually increases, DCR improves but high-temperature cycling deteriorates; when a / (b+t0)≥4, high-temperature cycling deteriorates significantly, worse than the data shown in Comparative Example 1.
[0111] The data in Table 2 shows that the dosage of additives A and B must satisfy 0.25 ≤ a / (b+t0) ≤ 4 to balance DCR and high-temperature cycling performance; otherwise, both DCR and high-temperature cycling performance will deteriorate simultaneously. Examples 24 to 32 list several combinations of additives A2 to A10 with different additives B, showing the most significant effects. The comparison reveals that the combination of additives A5 and B12 shows the most significant improvement in high-temperature cycling performance, but its improvement in DCR is slightly less than that of the combination of additives A8 and B8.
[0112] The results of Examples 33 to 35 show that the effects of different combinations of additives A and B are greater than those of single additives A and B; among them, the combination of additive A4 + additive A5 and additive B5 + additive B12 improved the high-temperature cycling performance to 89.4%, while the DCR deterioration effect was significantly suppressed.
[0113] Unless otherwise specified, the terms used in this invention have the meanings commonly understood by those skilled in the art.
[0114] The embodiments described in this invention are for illustrative purposes only and are not intended to limit the scope of protection of this invention. Those skilled in the art can make various other substitutions, changes and improvements within the scope of this invention. Therefore, this invention is not limited to the above embodiments, but is only defined by the claims.
Claims
1. An electrolyte, characterized in that, It includes additive A and additive B, wherein additive A is selected from one or more compounds of formula I, and additive B is selected from one or more nitrogen-containing heterocyclic compounds; R1, R2, R3, and R4 are independently selected from methyl, ethyl, propyl, methoxy, or -(-CH2-)n1-(-O-(-CH2-)n2-)n3-(-CH2-)n4-CH3, and at least one of R1, R2, R3, and R4 is selected from -(-CH2-)n1-(-O-(-CH2-)n2-)n3-(-CH2-)n4-CH3; n1 is an integer from 0 to 5, n2 is an integer from 1 to 3, n3 is an integer from 1 to 5, and n4 is an integer from 0 to 5. The nitrogen-containing heterocyclic compound is selected from one or more compounds with the structure of formula II-1, formula II-2, and formula II-3. Among them, R5, R6, R7, R8, R9, R 10 R 11 R 12 R 13 R 14 R 15 R 16 R 17 Each can be independently one of hydrogen group, fluorine group, methyl group, or trifluoromethyl group; The total mass percentage a of additive A in the electrolyte and the total mass percentage b of additive B in the electrolyte satisfy the following: 0.25≤a / (b+t0)≤4, where t0=0.01%, 0.05%≤a≤2%, and 0.05%≤b≤2%.
2. The electrolyte according to claim 1, characterized in that, Additive A is selected from one or more of the following compounds: 。 3. The electrolyte according to claim 1, characterized in that, The additive B is selected from one or more of the following compounds: 。 4. The electrolyte according to claim 1, characterized in that, The electrolyte comprises at least two of the additive compounds A, and / or at least two of the additive compounds B.
5. The electrolyte according to claim 1, characterized in that, 0.1%≤a≤1.6%, 0.1%≤b≤1.6%.
6. The electrolyte according to claim 1, characterized in that, The electrolyte further includes a solvent, a lithium salt, and an additive C, wherein the weight of the lithium salt is 10-20% of the total weight of the electrolyte; The additive C is selected from one or more of the following: fluoroethylene carbonate, vinylene carbonate, methylene disulfonate, 1,3-propane sulfonyl lactone, 1,4-butane sulfonyl lactone, 1,3-propene sulfonate lactone, ethylene sulfate, propylene sulfate, sulfone, and polyethersulfone.
7. The electrolyte according to claim 6, characterized in that, The lithium salt includes one or more of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl)imide, lithium difluorophosphate, lithium difluorooxalate borate, lithium difluorooxalate phosphate, lithium bis(fluorosulfonyl)imide, lithium methanesulfonate, lithium bis(oxalate borate), and lithium perchlorate.
8. A lithium-ion battery, characterized in that, It includes a negative electrode, a positive electrode, a separator, and the electrolyte as described in any one of claims 1-7.
Citation Information
Patent Citations
Silicon-based negative electrode lithium ion battery non-aqueous electrolyte and silicon-based negative electrode lithium ion battery containing the same
CN109921092A
Electrolyte, battery monomer, battery and electric device
CN117080564A
